Respuesta fisiológica de tres dosis de Trihormonas en el cultivo de la Col china (Brassica pekinensis) variedad Kiboho 90 f-1 en el distrito de Lamas - Ramírez Culquicondor, Marco (2013)
This research work entitled "physiological responses of three doses of Trihormona in the cultivation of Chinese cabbage (Brassica pekinensis.), variety kiboho 90 F-1 in the district of Lamas", had as objective to assess and analyze the production under the effect of 3 doses of Trihormona Agrostemín GL, and perform economic analysis of the treatments studied. The implementation of the Trihormona Agrostemin GL, was carried out 3 times to the 11; 40; and 55 days after sowing, using the statistical design of complete block design (RCBD), with four treatments and four replications. The results indicate that the treatments T3 (300 cc/ha of Trihormona Agrostemin GL), T2 (200 cc/ha of Trihormona Agrostemin GL), T1 (100cc/ha of Trihormona Agrostemin GL), T0 (witness) with averages of 89 693 kg.ha-1; 87 703 kg ha-1; 84 948 kg ha-1 and 75 866 kg ha-1; performance respectively, the Trihormona Agrostemín GL, had a relevant action that stimulated growth and structural development of the plant, consequently increase crop production. The higher the dose of implementation of Trihormona Agrostemin GL, the higher the average reached for plant height, weight pela, pela diameter and the performance in kg.ha-1. All treatments with doses of Trihormona Agrostemin GL, threw indices of B/C T1:5,94; T2:7,17; T3:7,34, which meant that the benefits (income) were higher than your expenses and in consequence the treatments generated wealth, the witness who threw a cost/ benefit of 4,20 by defining an average profitability.